Supply Chains In Indonesia Facing Virus Corona (COVID-19): Models Innovation And Obstacles Faced - Basrowi, Basrowi; Utami, Pertiwi; Ali, Juhary; Salleh, Muhammad Syukri (Bina Bangsa International Journal of Business and Management, 2021)
The purpose of this research is to reveal the innovation model and obstacles faced by the Indonesian government in handling the Covid-19 epidemic case. Based on previous research, supply chain management is needed because supply chain disruptions and inventory depletion (such as medical supplies and medical equipment) both in high and low resource settings have catapulted the core components of IPC 8 (environment, materials, and equipment for IPC). The research method used is qualitative, especially phenomenology. The novelty of this research lies in the innovation of the supply chain model and the Covid-19 handling constraints obtained through a series of empirical studies and literature reviews that allow it to be used by decision makers. The results revealed that various innovations to meet the supply chain relating to the handling of Covid-19 have been carried out by the government ranging from the creation of special hospitals, the appointment of public hospitals to the referral hospitals specifically Covid-19, the purchase of medicines from other countries that were imported , a mask development company, increases mask production for state-owned and private companies that produce masks, increases alcohol production, and recruits human resources in the health sector, especially for final year students majoring in health. While various obstacles faced, namely the low awareness of the community to do social distinguish in daily interactions, low awareness of the community to work from home, learn from home, and worship at home and the many people who have to work outside the home when they want to fulfill the day their daily needs, the threat of an unemployment explosion, and fears of social insecurity are also the causes of government difficulties in making locked decisions